The Feedback Given by University Supervisors to Student Teachers During Their Co-assessment Meetings - Maes, Olivier; Van Nieuwenhoven, Catherine; Colognesi, Stéphane (Frontiers in Education, 2022)
This qualitative study examines the levels of feedback given by university supervisors to student teachers during their co-assessment meeting in French-speaking Belgium. For this purpose, 14 co-assessment meetings were qualitatively analyzed. The co-assessment meeting is the final step in the internship supervision process and allows the student teacher to compare their self-evaluation with the cooperating teacher’s evaluation report and the supervisors’ evaluation. The analysis showed that the certification objective of the internship meeting influenced the level of feedback. Within this objective, the feedback was task-oriented. In the formative part of the meeting, the feedback was more process-oriented and self-regulatory. In this type of meeting, supervisors therefore adopt a dual perspective for feedback, both cognitivist and socio-constructivist. This dual perspective is part of a continuum logic.